The Efficiency of the Insurance Sector in the Kingdom of Saudi Arabia and its Impact on Economic Growth during the period 1995–2022 (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study has a twofold. First, it aimed to measure the efficiency of the insurance sector in the Kingdom of Saudi Arabia during the period 1995-2022. Efficiency was measured using the Data Envelopment Analysis (DEA) method, employing three inputs: general and administrative expenses, underwriting costs, and direct written premiums, and one output represented by the insurance operations surplus. The study also relied on the Malmquist Index to calculate and determine the nature of changes in the total factor productivity (TFP) of insurance companies. The results showed that only one company, Inaya Saudi Arabia Cooperative Insurance, achieved the optimal level of efficiency. Furthermore, the Malmquist Index results indicated a slight decrease in overall productivity, accompanied by a decline in pure technical efficiency and a reduction in scale efficiency. The Second objective of the research was the study of the impact of insurance sector efficiency on economic growth using the Autoregressive Distributed Lag (ARDL) model. Three models were estimated, considering three indicators of efficiency: insurance sector efficiency under constant returns to scale (CRS), under variable returns to scale (VRS), and the Malmquist Productivity Index. The findings revealed a long-run relationship between the efficiency of the insurance sector and economic growth. In the short run, the Error Correction Model (ECM) showed that efficiency has a negative and significant effect in both the CRS and VRS models, while its effect was positive and significant in the productivity index model. The causal relationships between insurance sector efficiency and economic growth were apprehended using the Toda-Yamamoto method. The results indicated a bidirectional causal relationship between insurance sector efficiency and economic growth in the constant returns to scale (CRS) model. In contrast, the variable returns to scale (VRS) model showed no causal relationship. The Malmquist Index model demonstrated the broadest connection with economic variables and the largest number of causal relationships directed toward economic growth among the models.Our results would have several prominent implications for policymakers when designing strategies to improve the performance and efficiency of the insurance sector, consistent with the economic diversification strategy outlined by the Kingdom in its Vision 2030.
Keywords: Insurance; Efficiency; DEA; ARDL; Growth; Saudi Arabia